Analysis of h-index and other bibliometric markers of productivity and repercussion of a selected sample of worldwide emergency medicine researchers. Issue 3 (26th August 2016) - Miró, Òscar; Burbano, Pablo; Graham, Colin A; Cone, David C; Ducharme, James; Brown, Anthony F T; Martín-Sánchez, Francisco Javier
Abstract : Objective: To explore bibliometric markers in a worldwide sample of emergency physician investigators to define global, continental and individual patterns over time. Methods: We evaluated the number of papers published, citations received, cumulative impact factor and h-index of editorial board members of six international emergency medicine journals. We calculated the individual values for every year of each author's career to evaluate their dynamic evolution. We analysed the results by researcher world area and growth rate. Results: We included 107 researchers (76 American, 21 European and 10 Australasian; 46 slow-rate -group C-, 43 medium-rate -group B- and 18 fast-rate growth -group A-). The median experience was 18 (IQR: 12) years, without subgroups differences. Dynamic analysis over time showed good fit with quadratic function in all individual researchers and for all bibliometric markers (R 2 : 0.505–0.997), with the h-index achieving the best R 2 . The combined analysis of the h-index of the 107 investigators also fit the quadratic model (R 2 =0.49). Analysis by predefined continental and growth-rate subgroups allowed defining specific patterns (R 2 between 0.46–0.54 and 0.80–0.86, respectively): by continents, American researchers' h-index increased 0.632 points per year, European 0.417 and Australasian 0.341; by growth rate, researchers from group A, B and C increased 1.239, 0.683 and 0.320, respectively. Conclusions: Dynamic analysis of every individual author indicator over time has a very good fit with a quadratic model, with the h-index achieving the best R 2 . It is also possible to construct models based on continent and rate of growth that could help to predict future expected outcomes of researchers in a particular subgroup and to classify new emerging researchers by growth rate.